Output feedback synchronization of euler-lagrange systems - Çiçek, Elif (My University, 2019)
This dissertation is devoted to offer a comprehensive control structure for tracking synchronization of Euler-Lagrange systems. For this purpose, three different output-feedback control mechanisms are developed for uncertain systems. Assuming that only position measurement is available, a linear-filter is suggested to obtain a surrogate signal, instead of actual velocity errors. Linear-filter output signals and the position errors are shared over a directed communication, in the presence of variable time-delay. In the first part of the study, a Lyapunov-based stability analysis using Lyapunov-Krasovskii functionals is performed to show that designed adaptive output-feedback controller yields a semi-global asymptotic convergence of error signals to zero. In the second part, it is proven that suggested robust output-feedback controller ensures semi-global asymptotic convergence of error signals to an adjustable hyperball around zero. The synchronization of kinematically redundant systems is also considered. It is shown that the suggested output feedback controller provides tracking synchronization on Cartesian space. The analysis results are supported by presented simulation and experimental studies.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Synchronization; Uncertain systems; Output-feedback control; Euler-Lagrange systems; Time-varying communication delay